Preparation method of hollow fiber membrane for degassing
Through the multi-step processing in the preparation method, the physical properties of the polyolefin are controlled, and hollow fiber membranes with dense outer surfaces and porous inner surfaces are formed, which solves the problems of diluent residue and short service life, and achieves high porosity and gas passage Improvement of rate and mechanical strength.
Patent Information
- Application Number
- CN202210810867.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-11
- Publication Date
- 2025-01-14
AI Technical Summary
The hollow fiber membrane prepared by the existing thermal phase separation method has diluent residue that affects the quality of ultrapure water, and the micropore structure that penetrates the inside and outside leads to a short service life.
A method of preparing a hollow fiber membrane for degassing is adopted, including spinning, precrystallization, air-cooled crystallization, annealing setting, cold-pullization pore formation, thermal-pullization pore expansion and thermal setting steps, by controlling the crystallinity and melting index of the polyolefin and die extrusion temperature to form a dense outer surface and a porous inner surface, improving mechanical properties and gas passing rate.
The prepared hollow fiber membrane has high porosity, high gas passing rate and high mechanical strength, which extends service life and improves the performance uniformity and production efficiency of the membrane.
Smart Images

Figure CN119303454A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of degassing membrane materials, and in particular to a method for preparing a hollow fiber membrane for degassing. Background Art
[0002] Polyolefins are a type of polymer material with large production and wide application because of their abundant raw materials, low price, easy processing and excellent comprehensive performance. Polyolefins have the characteristics of low relative density, good chemical resistance and water resistance. Polyolefins can be used for films, pipes, plates, various molded products, wires and cables, etc.
[0003] Degassing membrane is a membrane separation product that removes gases such as carbon dioxide, oxygen, and ammonia nitrogen from liquids. At present, the main methods for preparing such membranes are stretching pore-inducing method and thermally induced phase separation method. Among them, the stretching pore-inducing method is to make a crystalline polymer into a hollow fiber membrane or a thin film by melt extrusion, and then to make the polymer biaxially stretched along the extrusion direction by post-treatment to improve the shape and size of the membrane pores and the porosity; the thermally induced phase separation method is that some polymer materials cannot be dissolved at room temperature, and when the temperature is raised to above its melting point, they can form a uniform solution with some small molecular compounds (diluents). After cooling, the homogeneous solution undergoes solid-liquid or liquid-liquid phase separation and solidifies, and a microporous material is obtained after removing (diluent).
[0004] Patent CN107998903A discloses a method for preparing a polypropylene hollow fiber microporous membrane used in the field of membrane distillation and membrane degassing. The patent uses polypropylene as a raw material, high-grade fatty amine ethylene oxide adduct as a diluent, and a thermally induced phase separation method to obtain a polypropylene hollow fiber microporous membrane. The hollow fiber microporous membrane prepared in the patent has a through, sponge-like microporous structure section and a microporous distribution surface.
[0005] The above patent uses a thermo-induced phase method to prepare a porous hollow fiber membrane with internal and external penetration. The hollow fiber membrane prepared by the thermo-induced phase method needs to add a diluent, and the final hollow fiber membrane must have diluent residues. During the degassing process of ultrapure water, this part of the residue is prone to dissolution reaction, which has a great impact on the quality of ultrapure water. Therefore, the filter membrane prepared by the thermo-induced phase method is not suitable for the preparation of ultrapure water. In addition, although the porous hollow fiber membrane that penetrates inside and outside has a good degassing effect, the microporous structure that penetrates inside and outside makes it easy for fluid to flow in. Once the fluid flows in, the membrane will lose its ability to separate gas and liquid, and its service life is relatively low.
[0006] Through continuous exploration by technicians in this field, asymmetric hollow fiber membranes have shown excellent performance. Asymmetric hollow fiber membranes have a dense outer surface (no pore structure can be observed or a very small number of pore structures can be observed) and a porous support layer. The dense outer surface can effectively prevent fluid from flowing into the hollow fiber membrane and thus reduce its service life. However, the current preparation process of asymmetric hollow fiber membranes is not mature. How to prepare an asymmetric hollow fiber membrane with high porosity, high mechanical strength and long service life is one of the problems that technicians in this field need to solve urgently. Summary of the invention
[0007] In order to solve the above problems, the present invention aims to provide a method for preparing a hollow fiber membrane for degassing. The hollow fiber membrane prepared by the preparation method of the present application has high porosity and high gas permeability, which can meet actual needs. In addition, it can also meet good mechanical properties and extend the service life.
[0008] To achieve the above object, the present invention provides the following technical solutions:
[0009] A method for preparing a hollow fiber membrane for degassing comprises the following steps:
[0010] S1, spinning, extruding the polyolefin melt to form a semi-molded product with a hollow inner cavity under the action of a cavity-forming fluid;
[0011] The polyolefin is a homopolymer, has a crystallinity greater than 40%, a melt index of 1-7 g / min@(Tm+20°C, 5kg), a die extrusion temperature of (Tm+10)-(Tm+40)°C, and a die aspect ratio of 2-5;
[0012] The melting point of the polyolefin is Tm, and the polyolefin is at least one of PP, PE and PMP;
[0013] S2, pre-crystallization, cooling the semi-formed product obtained in step S1 by air cooling to obtain a pre-crystallized semi-finished product;
[0014] S3, air-cooling crystallization, performing secondary cooling crystallization on the pre-crystallized semi-finished product obtained in step S2 by means of air cooling, and winding to obtain a cooled semi-finished product;
[0015] S4, annealing and shaping, subjecting the cooled semi-finished product obtained in step S3 to heat shaping treatment, and obtaining a heat-set semi-finished product after cooling;
[0016] S5, cold drawing to form holes, cold drawing the heat-set semi-finished product obtained in step S4 to obtain a cold-drawn semi-finished product;
[0017] S6, hot-drawing and hole-expanding, hot-drawing and hole-expanding the cold-drawn semi-finished product obtained in step S5 to obtain a hot-drawn semi-finished product;
[0018] S7, heat setting, subjecting the hot-drawn semi-finished product obtained in step S6 to secondary heat setting treatment, and obtaining a hollow fiber membrane after cooling.
[0019] In the present application, polyolefin is melt-treated and then extruded, and a cavity-forming fluid is introduced at the same time to form an unshaped semi-finished product, wherein the introduction of the cavity-forming fluid can effectively avoid the concave deformation of the semi-finished product; then the semi-finished product is initially shaped by air cooling to form a pre-crystallized semi-finished product. The pre-crystallized semi-finished product is cooled and crystallized by blowing cooling, which has a suitable cooling temperature, cooling length and wind speed, so that it is crystallized and has a suitable crystallinity, and is rolled up after reaching a suitable winding temperature to obtain a cooled semi-finished product. The cooled semi-finished product is annealed to eliminate internal defects. The cooled semi-finished product is cold-drawn, and the present application uses a rapid cold-drawing method to stretch and form holes to obtain a cold-drawn semi-finished product. After cooling and stretching to form holes, the holes formed will rebound and shrink, so that the average pore size is reduced and the thickness is increased. Therefore, the cold-drawn semi-finished product is subjected to a hot-drawing expansion treatment to have a suitable average pore size, resulting in a suitable gas flow rate. Finally, a heat setting treatment is performed, and the holes and film thickness formed are set at a suitable temperature and time. Among them, it should be noted that the main function of cold drawing is to pull the lamellae apart and form the initial microfiber tie structure, while the main function of hot drawing is to expand the micropores generated in the cold drawing stage, increase the separation of the lamellae and make the microfiber tie structure more stable. The prepared hollow fiber membrane has a porous inner surface and a dense outer surface, wherein the dense outer surface is photographed by a scanning electron microscope at 100,000 times, and the pore area ratio of its outer surface (i.e., pore area: outer surface area) is not more than 5%, that is, there are two situations in which there is no observable pore structure or a very small number of pore structures can be observed.
[0020] The physical properties of the raw materials are the basis of the surface properties and microporous morphology of the microporous membrane. The crystallinity and melt index of the raw materials have a great influence on the performance of the membrane. In the present application, the polyolefin is a homopolymer, wherein the homopolymer is a polymer formed by polymerization of a monomer, and has the advantages of high crystallinity, good mechanical strength and heat resistance. The present application increases the crystallinity and mechanical properties from the raw materials, thereby increasing the crystallinity and mechanical strength of the prepared membrane, and further increasing the porosity and tensile strength of the membrane. The crystallinity of the polyolefin is greater than 40%, and the present application is preferably 45-75%. A smaller crystallinity reduces the porosity of the prepared membrane, thereby reducing the gas permeability; while an excessively large crystallinity increases the porosity, which reduces the mechanical properties of the prepared membrane. The crystallinity selected in the present application ensures the porosity of the prepared membrane, while also having good mechanical properties. The present application uses the DSC method to measure its crystallinity.
[0021] Among them, the full name of the melt index is the melt flow index, or melt flow index, which is a value that indicates the fluidity of the material during processing; the measurement method is: first, let the material particles melt into a fluid, and then within a certain period of time, at a certain temperature and pressure (different standards for various materials), finally flow out from a round tube of a certain diameter, and measure its number of grams (g). The larger the melt index value, the better the processing fluidity of the material, and vice versa. When the melt index is small, the obstacles to the arrangement of molecular chains increase, the molecular chains diffuse, and the activation energy required for the crystal phase structure increases, resulting in a decrease in the ability of the molecular chains to arrange regularly, thereby reducing the crystallinity. When the melt index is large, the plasticity of the material deteriorates and it is not easy to form. The melt index of this application is 1-7g / min@(Tm+20℃, 5kg), which makes the polyolefin have a higher degree of crystallinity and increases the porosity of the hollow fiber membrane; at the same time, it has good processing fluidity, makes the membrane thickness more uniform, improves the raw material processing efficiency, and reduces energy consumption and production costs.
[0022] The die extrusion temperature of the present application is (Tm+10)-(Tm+40)℃, that is, the temperature of the polyolefin extruded at the die is 10-40℃ above the melting point of the polyolefin, preferably 15-38℃ above the melting point of the polyolefin. The flow viscosity of the polymer melt is significantly affected by temperature, and the general viscosity decreases with the increase of temperature. When the die extrusion temperature is too low, the viscosity of the polyolefin increases, the resistance of the extrusion die increases, the energy consumption of the extrusion process increases, and the thickness of the prepared film increases, and the expansion and stretching cannot be better performed, thereby affecting the tensile strength of the film; when the die extrusion temperature is too high, it is not only easy to cause thermal degradation of the polyolefin, but also to break the main chain of the polyolefin from the weak bond in the middle, thereby reducing its molecular weight, significantly reducing the mechanical properties, and thereby reducing the mechanical properties of the film; it is also easy to increase the segment activity of the polymer molecules, expand the "free volume" of the melt, increase the fluidity of the melt, reduce its viscosity, and reduce the thickness of the prepared film, thereby affecting the gas throughput. The suitable die extrusion temperature and melt index of the present application make the thickness of the prepared film more uniform, and ensure both good porosity and strong mechanical properties.
[0023] The die head aspect ratio is the ratio of the effective length of the screw to the screw diameter. When the aspect ratio is smaller, the free volume of the extruder is reduced, and the outlet expansion effect is greater, so that the macromolecules are less subject to shear force in the pores, the fewer regular structures are formed, the crystallinity is reduced, and the number of holes in the prepared membrane is reduced, which in turn affects the porosity of the membrane; at the same time, it is impossible to effectively solve the orifice expansion phenomenon generated during the spinning process, which in turn affects the spinning speed, the thickness of the membrane and the mechanical properties of the prepared membrane. The orifice expansion phenomenon, also known as the Balas effect, refers to the fact that when a polymer fluid is extruded from a small hole, capillary or slit, the diameter or thickness of the extrudate will be significantly larger than the size of the orifice. When the aspect ratio is too large, the pressure applied by the screw is too large, affecting the performance of the prepared membrane.
[0024] The die aspect ratio of the present application is 2-5. When the molten polyolefin flows in the spinneret, the macromolecular chain is oriented by the shear force. The larger the aspect ratio, the longer the time for the polyolefin melt to be subjected to the shear force, so that the macromolecular chain is arranged more regularly. The regular macromolecular structure formed under the shearing action in the channel will not disappear due to the sudden expansion at the die outlet. The polyolefin macromolecular chain has a large crystallinity, a relatively perfect crystal structure, and a strong bonding force between macromolecules, so that the prepared film has good crystallinity. Therefore, the appropriate die aspect ratio not only has a suitable crystallinity, but also has a uniform film thickness, so that the prepared film has a more uniform hole structure and a larger tensile strength.
[0025] In summary, since the polyolefin of the present application has suitable crystallinity and melt index, as well as suitable die extrusion temperature and die aspect ratio, the prepared film has a more uniform film thickness and a larger crystallinity, and the film has a uniform pore structure, a larger tensile strength and a gas flow rate.
[0026] In the present application, the polyolefin is at least one of PP, PE and PMP, preferably PP; the cavity forming fluid can be in liquid or gaseous form, wherein the gaseous form can be nitrogen or inert gas, and nitrogen is preferred in the present application.
[0027] Furthermore, in step S1, the molecular weight of the polyolefin is 60,000-100,000, and the polyolefin distribution index is 1-5; the melting process includes: melting, mixing and metering, the melting temperature is (Tm-10)-(Tm+80)°C, the mixing temperature is (Tm+10)-(Tm+100)°C, and the metering temperature is (Tm+15)-(Tm+90)°C.
[0028] It should be noted that for low molecular weight substances, the molecular weight is a clear value after the molecular structure is determined, but this is not the case for high molecular weight compounds. Due to the complexity of the polymerization process, the molecular weight of the product has a certain distribution, so the molecular weight is not uniform, that is, the molecular weight has polydispersity. Due to the polydispersity of molecular weight, the average molecular weight alone is not enough to characterize the size of polymer molecules, because when the average molecular weight is the same, the molecular weight distribution may be quite different. Molecular weight distribution refers to the relationship between the relative content of each component in a polymer sample and the molecular weight.
[0029] Different molecular weights and molecular weight distributions have certain effects on crystallinity and crystal nucleus size. The molecular weight polydispersity shows that there is an obvious interaction between high and low molecular weight components. When the molecular weight distribution is wide, the interaction between high and low molecular weight components increases. Due to the different crystallization rates of high and low molecular weight components, the low molecular weight component crystallizes quickly and crystallizes first, causing the polymer chains that crystallize first to "freeze" the polymer chains that are not crystallized, thereby reducing the crystallinity. At the same time, the rapid crystallization of the low molecular weight component limits the growth of the crystal nucleus, resulting in a decrease in the size of the crystal nucleus, making the formed pores smaller, and thus reducing the gas throughput. If the molecular weight distribution becomes narrower, the interaction between high and low molecular weight components decreases, and crystallization occurs at a similar rate, which is conducive to the generation of crystal nuclei and makes the distribution of crystal nuclei uniform, thereby making the pore distribution of the prepared hollow fiber membrane more uniform, and thus having a suitable porosity and greater mechanical properties, resulting in a suitable gas throughput and greater tensile strength.
[0030] Therefore, the polyolefin in the present application has a suitable molecular weight of 60,000-100,000, and a narrow molecular weight distribution of 1-5, so that the crystal nucleus distribution in the process of preparing the hollow fiber membrane of the present application tends to be uniform, and the pore distribution of the prepared membrane is relatively uniform, so that it has a suitable porosity and greater mechanical properties, a suitable gas flow rate and a greater tensile strength.
[0031] In the meltblowing process, after the polymer solid enters the meltblowing equipment system from the hopper, it first passes through the screw extruder, then through the metering pump, reaches the spinning box, i.e. the die assembly, and is finally extruded from the spinneret hole. In this process, the melt of the present application mainly undergoes: melting, mixing and metering.
[0032] Among them, the melting section is mainly responsible for the transportation, pushing and preheating of the raw materials. The preheating temperature is above the melting point of the raw materials so that the raw materials gradually melt and finally become completely molten. If the temperature of this section is too high, the raw materials are easy to decompose, and if the temperature is too low, the raw materials will not melt completely. The temperature of the melting section of this application is set to (Tm-10)-(Tm+80)℃, which can make the raw materials in a more suitable molten state. The mixing section is mainly responsible for the mixing, compression and pressurized exhaust of the raw materials. All the raw materials passing through this section are in a molten state. If the temperature of this section is too high, the raw materials are easy to decompose, and if the temperature is too low, the melting effect is poor, which in turn affects its fluidity. The temperature of the mixing section of this application is set to (Tm+10)-(Tm+100)℃, which can make the raw materials have a more suitable molten state, and achieve better effects of mixing, compression and pressurized exhaust, and avoid uneven distribution of holes in the prepared membrane.
[0033] The main functions of the metering section are mixing, melting, and conveying. It also provides sufficient pressure to maintain a uniform temperature of the melt and a stable melt flow rate. Too high a temperature will cause the raw materials to decompose, and too low a temperature will result in poor melting effect. The temperature set in the metering section of this application is (Tm+15)-(Tm+90)°C, which can make the raw materials reach a more suitable melting state in the metering section and have a better melt flow rate; the metering temperature is at least 5-30°C higher than the extrusion temperature of the die head. When the polyolefin is extruded from the die head, heat conduction occurs inside, causing its temperature to drop. During the cooling process, the temperatures of the inner and outer surfaces are more uniform, ensuring more uniform crystallization, and thus ensuring more uniform pores in the prepared membrane.
[0034] Further, in step S1, when the polyolefin is PP, the isotacticity of the PP is greater than 99%, the crystallinity is 45-75%, and the melt index is 2-5 g / min@(190, 5 kg); or, when the polyolefin is PE, the PE is mLLDPE, and the density of the mLLDPE is 0.91-0.93 g / cm 3 , the molecular weight distribution index is 2-2.5, and the degree of branching is 0.1-0.4; or, when the polyolefin is PMP, the Vicat softening point of the PMP is 160-170°C.
[0035] The polyolefin of the present application is preferably PP, and the isotacticity of PP is greater than 99%. Among them, the isotacticity refers to the percentage of isotactic and syndiotactic polymers in the polymer to the total percentage of all polymer molecules. The larger the isotacticity, the better the symmetry of the PP, the polymers with no or few branches or small side groups, and the large intermolecular forces are easy to be close to each other, making it easier to crystallize, and then have better crystallinity in the process of preparing hollow fibers. The PP of the present application has a suitable crystallinity and melt index, so that the PP has good processing fluidity, so as to improve the raw material processing efficiency, reduce energy consumption and production costs, and at the same time make the thickness of the prepared membrane more uniform, so that the holes formed by the membrane are more uniform, so that the prepared hollow fiber membrane has a better porosity and a better gas flow rate.
[0036] When the polyolefin in the present application is PE, it is preferably mLLDPE with a relatively regular molecular chain structure. When the branching degree of mLLDPE is high, the more short branches in the mLLDPE molecular chain, the greater the steric hindrance of molecular motion and orderly arrangement, and the lower the crystallinity. The mLLDPE of the present application has a suitable branching degree, so that it has a larger crystallinity. When the molecular weight distribution of mLLDPE is narrow, the intermolecular force is large, which is conducive to the confidential stacking of its molecular chain, so that the movement speed of each segment is closer, and its crystallinity is improved. The mLLDPE of the present application has a suitable molecular weight distribution index, so that it has a larger crystallinity. The density of the mLLDPE of the present application is 0.91-0.93g / cm3, wherein the density is determined by the concentration of the comonomer in the polyethylene chain. The comonomer concentration controls the number of short branches (whose length depends on the comonomer type) to control the resin density. Due to the lack of long branches in mLLDPE, the polymer is not entangled, and the pore size of the hole formed is avoided to be too large. In summary, the hollow fiber membrane prepared by mLLDPE in the present application has a high degree of crystallinity, a uniform pore size distribution and a small average pore size, and thus the hollow fiber membrane has a high porosity while ensuring mechanical strength. Wherein, the degree of branching refers to the density of branch points in a polymer chain or the length of a segment between adjacent branches or the relative molecular weight of a segment.
[0037] The Vicat softening temperature is the temperature at which a polymer sample such as engineering plastics and general plastics softens when placed in a liquid heat transfer medium under a certain load and a certain constant temperature rise condition. 2 The temperature when the pressure needle is pressed into the depth of 1mm. The softening point refers to the temperature when the amorphous polymer begins to soften. The main determination methods are Vicat method and ring and ball method. When the polyolefin of the present application adopts PMP, the Vicat softening point of PMP is 160-170℃, so that the hollow fiber membrane has good dimensional stability and small thermal deformation when heated, that is, good heat resistance and deformation resistance, high rigidity and high modulus.
[0038] Furthermore, in step S2, the air cooling temperature is 110-220° C. lower than the die head temperature, and the air cooling distance of the semi-finished product is 30-1000 mm.
[0039] In the present application, the air cooling temperature is 110-220°C lower than the die temperature, and the die extrusion temperature is higher than the melting point of polyolefin, so as not to affect the regularity of the surface, to avoid crystallization due to too low temperature affecting the crystallinity in the subsequent steps, so that the polyolefin is extruded in a molten state to form a semi-molded product, and the semi-molded product is cooled by air cooling to shape the semi-molded product. When the air cooling temperature is too low, the semi-molded product will directly form crystals during the shaping process, which will lead to uneven crystallization, reduce crystallinity, reduce porosity, and reduce flux. When the air cooling temperature is too high, the semi-finished product is not fully shaped, and the surface is prone to depression during the air-cooled crystallization process, which will affect the performance of the hollow fiber membrane. The present application adopts a suitable air cooling temperature so that crystals are not formed during the air cooling process and the shaping is complete.
[0040] Furthermore, in the step S3, the air-cooling length of the pre-crystallized semi-finished product is 4-8 m; the air-cooling temperature is 40-70° C.; and the relative speed of the airflow and the pre-crystallized semi-finished product during the air-cooling crystallization process is 30-60 m / min.
[0041] It should be noted that when the air-cooling temperature is too high, the outer surface cannot be cooled rapidly, and thus a dense surface cannot be formed, which not only reduces the mechanical strength of the hollow fiber membrane, but also affects the air throughput of the hollow fiber membrane. When the air-cooling temperature is too low, the area of rapid cooling along the membrane thickness direction increases, thereby increasing the thickness of the cortex, resulting in a decrease in the gas throughput of the hollow fiber membrane. The present application has a suitable air-cooling temperature, so that the hollow fiber membrane prepared therefrom not only has a large gas throughput, but also has a high mechanical strength.
[0042] The suitable cooling temperature of the present application allows the outer surface to be cooled rapidly, so that the outer surface forms a dense surface with a cortical area, but the inner surface is still in a high temperature state, and the air is blown to cool to a suitable length, so that the inner surface temperature drops to a temperature that can be rolled up within a reasonable length range, saving process costs.
[0043] During the air-cooled crystallization process, the relative speed between the airflow and the pre-crystallized semi-finished product is 30-60 m / min. If the relative speed is too fast, the outer surface is prone to collapse, which reduces the performance of the membrane; if the relative speed is too slow, the cooling speed is too slow, and the outer surface cannot form a dense surface, which in turn affects the performance of the membrane. The appropriate relative speed of the present application forms a dense surface on the outer surface of the membrane, and has appropriate gas throughput and mechanical properties.
[0044] Further, the hot-drawing temperature in step S6 is at least 60-95°C higher than the cold-drawing temperature in step S5; the hot-drawing speed is 5-15%, preferably 10%, of the cold-drawing speed; and the hot-drawing is 2-6 times the stretching multiple of the cold-drawing. In step S5, the cold-drawing temperature is 25-80°C higher than the glass transition temperature of the polyolefin; the cold-drawing speed is 10-30% / min, preferably 12-25% / min; and the cold-drawing stretching multiple is 20%-40%. In step S6, the hot-drawing temperature is 80-160°C; the hot-drawing stretching multiple is 80%-120%; and the hot-drawing speed is 0.3-1.3% / min, preferably 0.5-1 / min.
[0045] The cold drawing temperature of the present application is 25-80°C higher than the glass transition temperature of polyolefins, wherein the glass transition temperature is the temperature at which a polymer changes from a highly elastic state to a glassy state, and refers to the transition temperature of an amorphous polymer (including the non-crystalline part of a crystalline polymer) from a glassy state to a highly elastic state or from the latter to the former, and is the lowest temperature at which the macromolecular segments of an amorphous polymer can move freely. When the cold drawing temperature is high, adjacent crystal nuclei are prone to agglomeration, resulting in uneven pore sizes and uneven pore distribution of the hollow fiber membrane; when the cold drawing temperature is low, the fiber between adjacent crystal nuclei lacks elasticity when the temperature is low, and is prone to breakage, thereby affecting the performance of the membrane, reducing the mechanical strength, and affecting the filtering effect of the membrane. The present application has a suitable cold drawing temperature, so that the prepared hollow fiber membrane has a suitable average pore size, and the pores are evenly distributed, and at the same time has a strong tensile strength, so that the hollow fiber membrane has a good gas throughput.
[0046] For the dense surface, when the cold drawing rate is too high, the dense surface is subjected to a large tensile stress. Excessive tensile stress is easily concentrated at the defects of the dense surface, causing the dense surface to break locally and produce a microporous structure. Therefore, it is necessary to control the upper limit of the cold drawing rate. For the inner layer, when the cold drawing rate is too high, the tensile stress is also easily concentrated, causing the lamellae with a short relaxation time to first form a pore structure and further expand, while the lamellae with a long relaxation time have not yet separated, resulting in an uneven microporous structure. A too high cold drawing rate may even cause the microfiber bands in some pore structures to have broken, while the remaining lamellae have not yet separated, resulting in poor uniformity and uneven distribution of the microporous structure of the inner layer. When the cold drawing rate is too low, the lamellae in the inner layer have enough time to relax. At this time, part of the tensile stress is used to cause the lamellae in the inner layer to deform, and only part of the tensile stress is used to cause the deformation of the amorphous zone between the lamellae and the generation of microfiber bands. Due to the low degree of separation of the lamellae, the pore structure formed is small and the size is too small. In the present application, the cold drawing speed is 10-30% / min, so that the outer surface of the prepared hollow fiber membrane is a dense surface with a large porosity and uniform pore size distribution.
[0047] In the present application, the cold-drawing stretching ratio is 20%-40%. Due to the low temperature of cold-drawing, the elasticity of the polymer is relatively small. When the stretching ratio is large, the fiber is easily broken or the formed pores are too large, thereby affecting the mechanical properties of the membrane and the filtering effect of the membrane. When the stretching ratio is small, the formed membrane is thicker and the pores are smaller, thereby reducing the amount of gas passing through.
[0048] After cooling and stretching, the molecular chains inside the fiber will be oriented, and the molecular chain segment orientation can effectively improve the mechanical properties of the material, thereby improving the tensile strength of the fiber; the parallel layered lamellae structure in the hollow fiber is separated along the stretching direction to form micropores and microfibers. Therefore, by cold stretching, not only the strength of the fiber can be improved, but also a microporous structure can be formed. Only by coordinating the appropriate cold drawing temperature, the appropriate cold drawing rate and the appropriate cold drawing elongation, can the hollow fiber membrane with a dense surface and low thickness, high inner layer porosity and good pore structure required by the present application be obtained. Adjusting a certain process parameter alone cannot obtain the hollow fiber membrane structure required by the present application. Among them, the present application adopts multiple cold drawing, which can significantly improve the pore structure of the inner layer and the dense surface of the prepared hollow fiber, wherein the density of the dense surface is improved, and the porosity, pore structure, etc. of the inner layer are improved. It is preferably 2 cold drawing, and the 2 cold drawing have the same acceleration, so that the pores formed by stretching have a suitable average pore size, which has a suitable porosity and a suitable membrane thickness.
[0049] In the present application, the hot-drawing temperature is 80-160°C. When the hot-drawing temperature is high, the occurrence of heat-induced crystallization and tensile stress-induced crystallization promotes rapid crystallization of the fiber, resulting in the failure of the macromolecular chain segments to be fully stretched along the stretching direction. At the same time, the polymer molecular chain has been broken at high temperature, so that the effect of pore expansion cannot be achieved, and the tensile strength of the hollow fiber membrane is reduced. When the hot-drawing temperature is low, the temperature at which the polymer macromolecular chain segments can move freely cannot be reached, so that the semi-finished product has low elasticity, resulting in insufficient stretching, or fiber breakage during stretching, so that the effect of pore expansion cannot be achieved. The hot-drawing is carried out in a multi-stage, slow stretching and pore expansion manner, preferably 5 hot-drawings; and the speed of the hot-drawing is preferably 10% of the cold-drawing speed. Rapid cold-drawing at an appropriate speed can avoid the occurrence of stretching and breaking at too fast a speed, and can also make the crystal nucleus break quickly to form a more uniform size of the hole. The present application has a suitable hot-drawing temperature, and the hot-drawing temperature is at least 60-95°C higher than the cold-drawing temperature, which can achieve the ideal effect of stretching and pore expansion, and at the same time has a large tensile strength, a large gas throughput, and a good filtering effect.
[0050] When the hot pull rate is too low (it can be understood that the so-called hot pull rate here is based on the determination of the cold pull rate, and the hot pull rate is characterized by the multiple of the cold pull rate), the tensile stress has enough time to act on each area. At this time, the molecular chains of the lamellae and the molecular chains at the boundaries of the lamellae and the amorphous region have enough time to relax and be pulled out, so that part of the lamellae is converted into microfiber ligaments. There are too many microfiber ligament structures and too few lamellae structures, resulting in the deterioration of the microporous structure. When the hot pull rate is too high, the tensile stress is unevenly distributed, and the molecular chains with a long relaxation time have no time to transform, which ultimately results in only some molecular chains with a short relaxation time being converted into microfiber ligament structures, and the molecular chains at the boundaries of the lamellae and the amorphous region are easily overstretched, thereby blocking the generated microporous structure, resulting in the closure of the micropores and the deterioration of the microporous structure. In the present application, the hot stretching has a suitable stretching rate, so that the hollow fiber membrane has more lamellae structures during the preparation process, so that it has a larger porosity, thereby increasing the gas throughput.
[0051] The stretching ratio of the heat stretching of the present application is 80%-120%, wherein the stretching ratio refers to the ratio of the length of the fiber after stretching to the length before stretching. When the stretching ratio is high, the tensile stress is high, and the excessive tensile stress destroys the original ordered crystal region of the fiber and reduces the crystallinity of the fiber. When the stretching ratio is low, the expected membrane thickness and pore size cannot be achieved. The present application has a suitable stretching ratio, so that the prepared hollow fiber membrane has a suitable membrane thickness and pore size, and does not affect the crystallinity during the preparation of the hollow fiber membrane.
[0052] Cold drawing and hot drawing are interrelated and mutually influential processes. There is a high correlation between the process parameters of the two. They are not two isolated steps. For example, when adjusting the process parameters, the overall process parameters of the two must be adjusted uniformly.
[0053] Furthermore, in step S4, the annealing is performed to reduce the temperature to 75-150° C., the annealing time is 20-50 min, and the draft ratio is 0.5-2%;
[0054] In the step S7, the heat setting temperature is 80-160° C. and the heat setting time is 1-10 min.
[0055] It should be noted that the above definition can make the inner layer of the fiber have a higher crystallinity, good crystal regularity and orientation after annealing and shaping, so that a good pore structure can be obtained when stretching into holes, and when heat-setting, the residual stress in the inner layer of the fiber can be well eliminated, so that the fiber and the microporous structure on the fiber have a high degree of stability. As for the dense surface of the fiber, the specific annealing and shaping temperature can reduce the crystallinity, crystal orientation and regularity of the dense surface, thereby reducing the possibility of the dense surface generating a microporous structure during the stretching and shaping process, and during heat-setting, the higher temperature can not only eliminate the defects of the dense surface, but also promote the crystallization behavior of the dense surface, improve the crystallinity of the dense surface, and thus improve the mechanical properties of the dense surface.
[0056] The process parameters of annealing and heat setting are also interrelated. This is because the crystallinity, crystal form, regularity, etc. of the fiber after annealing have a great influence on the microporous structure of the fiber. Different sheet thickness, different microfiber tie size, etc. require different heat setting process parameters.
[0057] The present application can bring the following beneficial effects: compared with the existing hollow fiber membrane structure, the hollow fiber membrane provided by the present application has a more uniform membrane wall thickness, a higher crystallinity, a higher porosity, a higher gas throughput and a higher tensile strength. The performance of the hollow fiber membrane is greatly improved and its service life is extended. The preparation method provided by the present invention can conveniently, quickly and effectively prepare the above hollow fiber membrane. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0059] Figure 1 This is a scanning electron microscope (SEM) image of the inner surface of the hollow fiber membrane prepared in Example 1, wherein the magnification is 10000×;
[0060] Figure 2 This is a scanning electron microscope (SEM) image of the outer surface of the hollow fiber membrane prepared in Example 1, where the magnification is 30000×. DETAILED DESCRIPTION
[0061] In order to more clearly explain the overall concept of the application, the following is described in detail by way of embodiment. In the following description, a large amount of specific details are provided so as to provide a more thorough understanding of the application. However, it is obvious to those skilled in the art that the application can be implemented without one or more of these details. In other examples, in order to avoid confusion with the application, some technical features well known in the art are not described.
[0062] Unless otherwise specified, in the following examples, the raw materials and equipment used to prepare the hollow fiber membranes can be purchased from commercial sources. The structure and morphology of the membranes were characterized using a scanning electron microscope (S-5500) provided by Hitachi.
[0063] Example 1
[0064] Example 1 provides a method for preparing a hollow fiber membrane for degassing, and the specific steps are as follows:
[0065] S1. Spinning, melt-extrude PP, wherein the PP molecular weight is 80,000 and the PP molecular weight distribution index is 1.5; during the melting process, the melting temperature is 165°C, the mixing temperature is 200°C, the metering temperature is 205°C, the crystallinity is 50%, the melt index is 2g / min@(190°C, 5kg), the die extrusion temperature is 190°C, and the die aspect ratio is 3, and a semi-molded product with a hollow inner cavity is formed under the action of nitrogen.
[0066] S2, pre-crystallization, cooling the semi-formed product obtained in step S1 by air cooling, wherein the temperature is 80°C and the distance is 400mm, to obtain a pre-crystallized semi-finished product;
[0067] S3, air-cooled crystallization, the pre-crystallized semi-finished product obtained in step S2 is subjected to secondary cooling crystallization by means of air cooling, and rolled up to obtain a cooled semi-finished product, wherein the cooling length is 4.5 m, the temperature is 55° C., and the air flow velocity is 35 m / min.
[0068] S4, annealing and shaping, the cooled semi-finished product obtained in step S3 is subjected to heat shaping treatment to obtain a heat-set semi-finished product after cooling, wherein the temperature is reduced to 120° C., the time is 28 minutes, and the draft ratio is 0.7%.
[0069] S5, cold drawing to form holes, cold drawing the heat-set semi-finished product obtained in step S4 to obtain a cold-drawn semi-finished product; wherein the temperature is 40° C., the speed is 15% / min, and the stretching ratio is 25%.
[0070] S6, hot-drawing and hole-expanding, hot-drawing and hole-expanding the cold-drawn semi-finished product obtained in step S5 to obtain a hot-drawn semi-finished product; wherein the temperature is 120° C., the stretching ratio is 85%, and the speed is 0.5% / min.
[0071] S7, heat setting, subjecting the hot-drawn semi-finished product obtained in step S6 to secondary heat setting treatment, and obtaining a hollow fiber membrane after cooling; wherein the temperature is 135° C., and the time is 2.5 min.
[0072] Example 2
[0073] Example 2 provides a method for preparing a hollow fiber membrane for degassing, and the specific steps are as follows:
[0074] S1. Spinning, melt-extrude PP, wherein the PP molecular weight is 90,000, and the PP molecular weight distribution index is 2; the melting temperature in the melting process is 170°C, the mixing temperature is 190°C, the metering temperature is 210°C, the crystallinity is 55%, the melt index is 3g / min@(190°C, 5kg), the die extrusion temperature is 205°C, and the die aspect ratio is 3.5, and a semi-molded product with a hollow inner cavity is formed under the action of nitrogen.
[0075] S2, pre-crystallization, cooling the semi-formed product obtained in step S1 by air cooling for pre-crystallization, wherein the temperature is 90°C and the distance is 500mm, to obtain a pre-crystallized semi-finished product.
[0076] S3, air-cooled crystallization, the pre-crystallized semi-finished product obtained in step S2 is subjected to secondary cooling crystallization by means of air-blowing cooling, and rolled up to obtain a cooled semi-finished product, wherein the cooling length is 5 m; the temperature is 40° C.; and the air flow velocity is 48 m / min.
[0077] S4, annealing and shaping, the cooled semi-finished product obtained in step S3 is subjected to heat shaping treatment to obtain a heat-set semi-finished product after cooling, wherein the temperature is reduced to 135° C., the time is 45 minutes, and the draft ratio is 1.5%.
[0078] S5, cold drawing to form holes, cold drawing the heat-set semi-finished product obtained in step S4 to obtain a cold-drawn semi-finished product; wherein the temperature is 65° C., the speed is 22% / min, and the stretching ratio is 38%.
[0079] S6, hot-drawing and hole-expanding, hot-drawing and hole-expanding the cold-drawn semi-finished product obtained in step S5 to obtain a hot-drawn semi-finished product; wherein the temperature is 129° C., the stretching ratio is 110%, and the speed is 0.8% / min.
[0080] S7, heat setting, subjecting the hot-drawn semi-finished product obtained in step S6 to secondary heat setting treatment, and obtaining a hollow fiber membrane after cooling; wherein the temperature is 155° C., and the time is 1.6 min.
[0081] Example 3
[0082] Example 3 provides a method for preparing a hollow fiber membrane for degassing, and the specific steps are as follows:
[0083] S1. Spinning, melt-extrude PP, wherein the PP molecular weight is 100,000 and the PP molecular weight distribution index is 2.5; in the melting process, the melting temperature is 178° C., the mixing temperature is 201° C., the metering temperature is 196° C., the crystallinity is 65%, the melt index is 3.5 g / min@(190° C., 5 kg), the die extrusion temperature is 188° C., the die aspect ratio is 4, and a semi-molded product with a hollow inner cavity is formed under the action of nitrogen.
[0084] S2, pre-crystallization, cooling the semi-formed product obtained in step S1 by air cooling for pre-crystallization, wherein the temperature is 68° C. and the distance is 700 mm, to obtain a pre-crystallized semi-finished product.
[0085] S3, air-cooled crystallization, the pre-crystallized semi-finished product obtained in step S2 is subjected to secondary cooling crystallization by means of air-blowing cooling, and rolled up to obtain a cooled semi-finished product, with a cooling length of 6.8 m, a temperature of 68° C., and an air flow velocity of 52 m / min.
[0086] S4, annealing and shaping, the cooled semi-finished product obtained in step S3 is subjected to heat shaping treatment to obtain a heat-set semi-finished product after cooling, wherein the temperature is reduced to 110° C., the time is 50 minutes, and the draft ratio is 2%.
[0087] S5, cold drawing to form holes, cold drawing the heat-set semi-finished product obtained in step S4 to obtain a cold-drawn semi-finished product, wherein the temperature is 20° C., the speed is 30% / min, and the stretching ratio is 20%.
[0088] S6, hot-drawing and hole-expanding, hot-drawing and hole-expanding the cold-drawn semi-finished product obtained in step S5 to obtain a hot-drawn semi-finished product, wherein the temperature is 140° C., the stretching ratio is 120%, and the speed is 1% / min.
[0089] S7, heat setting, subjecting the hot-drawn semi-finished product obtained in step S6 to secondary heat setting treatment, and obtaining a hollow fiber membrane after cooling; wherein the temperature is 140° C., and the time is 3 minutes.
[0090] Example 4
[0091] Example 4 provides a method for preparing a hollow fiber membrane for degassing, and the specific steps are as follows:
[0092] S1. Spinning, melt-extrude PP, wherein the PP molecular weight is 85,000 and the PP molecular weight distribution index is 1.5; during the melting process, the melting temperature is 165°C, the mixing temperature is 200°C, the metering temperature is 205°C, the crystallinity is 45%, the melt index is 0.5g / min@(190°C, 5kg), the die extrusion temperature is 205°C, and the die aspect ratio is 3, and a semi-molded product with a hollow inner cavity is formed under the action of nitrogen.
[0093] S2, pre-crystallization, cooling the semi-formed product obtained in step S1 by air cooling for pre-crystallization, wherein the temperature is 80°C and the distance is 300mm, to obtain a pre-crystallized semi-finished product.
[0094] S3, air-cooled crystallization, the pre-crystallized semi-finished product obtained in step S2 is subjected to secondary cooling crystallization by means of air blowing cooling, and rolled up to obtain a cooled semi-finished product, wherein the cooling length is 4.5 m, the temperature is 80° C., and the air flow velocity is 20 m / min.
[0095] S4, annealing and shaping, the cooled semi-finished product obtained in step S3 is subjected to heat shaping treatment to obtain a heat-set semi-finished product after cooling, wherein the temperature is reduced to 120° C., the time is 28 minutes, and the draft ratio is 0.7%.
[0096] S5, cold drawing to form holes, cold drawing the heat-set semi-finished product obtained in step S4 to obtain a cold-drawn semi-finished product; wherein the temperature is 40° C., the speed is 15% / min, and the stretching ratio is 25%.
[0097] S6, hot-drawing and hole-expanding, hot-drawing and hole-expanding the cold-drawn semi-finished product obtained in step S5 to obtain a hot-drawn semi-finished product; wherein the temperature is 120° C., the stretching ratio is 85%, and the speed is 0.5% / min.
[0098] S7, heat setting, subjecting the hot-drawn semi-finished product obtained in step S6 to secondary heat setting treatment, and obtaining a hollow fiber membrane after cooling; wherein the temperature is 135° C., and the time is 2.5 min.
[0099] Example 5
[0100] Example 5 provides a method for preparing a hollow fiber membrane for degassing, and the specific steps are as follows:
[0101] S1, spinning, melt extruding mLLDPE, wherein the mLLDPE molecular weight is 60,000, the mLLDPE molecular weight distribution index is 2.3, the melting process includes a melting temperature of 165°C, a mixing temperature of 155°C, a metering temperature of 200°C, a crystallinity of 68%, a melt index of 4.5g / min@(130°C, 5kg), and a density of mLLDPE of 0.93g / cm 3, the degree of branching is 0.3, the die extrusion temperature is 180°C, the die aspect ratio is 3.5, and a semi-molded product with a hollow inner cavity is formed under the action of nitrogen.
[0102] S2, pre-crystallization, cooling the semi-formed product obtained in step S1 by air cooling for pre-crystallization, wherein the temperature is 70°C and the distance is 870mm, to obtain a pre-crystallized semi-finished product.
[0103] S3, air-cooled crystallization, the pre-crystallized semi-finished product obtained in step S2 is subjected to secondary cooling crystallization by means of air-blowing cooling, and rolled up to obtain a cooled semi-finished product, with a cooling length of 6.4 m, a temperature of 70° C., and an air flow velocity of 60 m / min.
[0104] S4, annealing and shaping, the cooled semi-finished product obtained in step S3 is subjected to heat shaping treatment to obtain a heat-set semi-finished product after cooling, wherein the temperature is reduced to 75° C., the time is 50 minutes, and the draft ratio is 2%.
[0105] S5, cold drawing to form holes, cold drawing the heat-set semi-finished product obtained in step S4 to obtain a cold-drawn semi-finished product; wherein the temperature is 15° C., the speed is 28% / min, and the stretching ratio is 35%.
[0106] S6, hot-drawing and hole-expanding, hot-drawing and hole-expanding the cold-drawn semi-finished product obtained in step S5 to obtain a hot-drawn semi-finished product; wherein the temperature is 78° C., the stretching multiple is 110%, and the speed is 1.2% / min.
[0107] S7, heat setting, subjecting the hot-drawn semi-finished product obtained in step S6 to secondary heat setting treatment, and obtaining a hollow fiber membrane after cooling; wherein the temperature is 80° C., and the time is 3 minutes.
[0108] Example 6
[0109] Example 6 provides a method for preparing a hollow fiber membrane for degassing, and the specific steps are as follows:
[0110] S1, spinning, melt-extrude PMP, the PMP molecular weight is 98,000, and the PMP molecular weight distribution index is 3.2; the melting temperature in the melting process is 280°C, the mixing temperature is 300°C, the metering temperature is 290°C, the crystallinity is 78%, the melt index is 5g / min@(240°C, 5kg), the die extrusion temperature is 260°C, the die aspect ratio is 4, and a semi-molded product with a hollow inner cavity is formed under the action of nitrogen.
[0111] S2, pre-crystallization, cooling the semi-formed product obtained in step S1 by air cooling for pre-crystallization, wherein the temperature is 140°C and the distance is 670mm, to obtain a pre-crystallized semi-finished product.
[0112] S3, air-cooled crystallization, the pre-crystallized semi-finished product obtained in step S2 is subjected to secondary cooling crystallization by means of air cooling, and rolled up to obtain a cooled semi-finished product, with a cooling length of 7.2 m; the air cooling temperature is 68° C.; and the air flow velocity is 52 m / min.
[0113] S4, annealing and shaping, the cooled semi-finished product obtained in step S3 is subjected to heat shaping treatment to obtain a heat-set semi-finished product after cooling, wherein the temperature is reduced to 145° C., the time is 45 minutes, and the draft ratio is 1.3%.
[0114] S5, cold drawing to form holes, cold drawing the heat-set semi-finished product obtained in step S4 to obtain a cold-drawn semi-finished product; wherein the temperature is 50° C., the speed is 25% / min, and the stretching ratio is 35%.
[0115] S6, hot-drawing and hole-expanding, hot-drawing and hole-expanding the cold-drawn semi-finished product obtained in step S5 to obtain a hot-drawn semi-finished product; wherein the temperature is 135° C.; the stretching ratio is 112%; and the speed is 1.1% / min.
[0116] S7, heat setting, subjecting the hot-drawn semi-finished product obtained in step S6 to secondary heat setting treatment, and obtaining a hollow fiber membrane after cooling; wherein the forming temperature is 170° C., and the time is 2.5 min.
[0117] Comparative Example 1
[0118] Comparative Example 1 provides a method for preparing a hollow fiber membrane for degassing, and the specific steps are as follows:
[0119] S1. Spinning, melt-extrude PP, wherein the PP molecular weight is 110,000, and the PP molecular weight distribution index is 1.5; the melting temperature in the melting process is 165°C, the mixing temperature is 200°C, the metering temperature is 205°C, the crystallinity is 30%, the melt index is 0.5g / min@(190°C, 5kg), the die extrusion temperature is 190°C, and the die aspect ratio is 1, and a semi-molded product with a hollow inner cavity is formed under the action of nitrogen.
[0120] S2, pre-crystallization, cooling the semi-formed product obtained in step S1 by air cooling for pre-crystallization, wherein the temperature is 80°C and the distance is 400mm, to obtain a pre-crystallized semi-finished product.
[0121] S3, air-cooled crystallization, the pre-crystallized semi-finished product obtained in step S2 is subjected to secondary cooling crystallization by means of air cooling, and rolled up to obtain a cooled semi-finished product, wherein the cooling length is 4.5 m; the temperature is 55° C.; and the air flow velocity is 35 m / min.
[0122] S4, annealing and shaping, the cooled semi-finished product obtained in step S3 is subjected to heat shaping treatment to obtain a heat-set semi-finished product after cooling, wherein the temperature is reduced to 120° C., the time is 28 minutes, and the draft ratio is 0.7%.
[0123] S5, cold drawing to form holes, cold drawing the heat-set semi-finished product obtained in step S4 to obtain a cold-drawn semi-finished product; wherein the temperature is 70° C., the speed is 30% / min, and the stretching ratio is 25%.
[0124] S6, hot-drawing and hole-expanding, hot-drawing and hole-expanding the cold-drawn semi-finished product obtained in step S5 to obtain a hot-drawn semi-finished product; wherein the temperature is 156° C., the stretching ratio is 85%, and the speed is 0.4% / min.
[0125] S7, heat setting, subjecting the hot-drawn semi-finished product obtained in step S6 to secondary heat setting treatment, and obtaining a hollow fiber membrane after cooling; wherein the temperature is 135° C., and the time is 2.5 min.
[0126] In Comparative Example 1, under the same conditions as other step parameters in Example 1, the crystallinity and melt index of PP were changed, so that the porosity of the hollow fiber membrane was reduced, the wall thickness uniformity of the hollow fiber membrane was increased, and the gas flow rate of the hollow fiber membrane was reduced.
[0127] Performance Experiment
[0128] 1. Structural Characterization
[0129] The inner and outer surface morphologies of the hollow fiber membranes obtained in each embodiment and comparative example were characterized, the average pore size of the inner surface of the main body, the thickness of the skin layer, and the outer diameter, inner diameter, porosity and wall thickness uniformity of the hollow fiber membrane were measured. The measurement data are shown in Table 1, and the morphology characterization results of Example 1 are shown in Figure 1-Figure 2 .
[0130] Table 1 Characterization of each example membrane structure
[0131]
[0132]
[0133] In Table 1, the wall thickness uniformity refers to the wall thickness of the hollow fiber membranes prepared in each embodiment or comparative example. Each hollow fiber membrane is cut into 4 sections, and the wall thickness is measured once for each section. The interval between each measurement is 20 cm. The maximum value of the wall thickness is recorded as dmax, and the minimum value of the wall thickness is recorded as dmin. The average wall thickness △d is calculated based on the four measured wall thicknesses. The wall thickness uniformity is calculated according to the following formula:
[0134]
[0135] The smaller the wall thickness uniformity is, the more uniform the thickness of the hollow fiber membrane is. Generally, the wall thickness uniformity is no more than 5%.
[0136] 2. Performance Test
[0137] The tensile properties of the hollow fiber membranes obtained in each example were tested.
[0138] Clamp the membrane filament vertically at the upper and lower ends of the chuck, and control the distance between the two ends of the chuck to be 5cm.
[0139] Select the mode on the operating instrument and operate the instrument to obtain the tensile strength and elongation.
[0140] Calculation results:
[0141] Tensile Strength:
[0142] Where: σ is the tensile strength, in megapascals (CN); Fb is the maximum force at break, in N; So is the original cross-sectional area of the specimen, in mm 2 ); it is represented by “sample area S” in the instrument.
[0143] Elongation:
[0144] Where: e is elongation; △L is the length increment between the gauge lengths of the specimen, in millimeters (mm); L is the gauge length of the specimen, in millimeters (mm).
[0145] Table 2 Tensile properties test results of each example
[0146]
[0147] The hollow fiber membranes obtained in each example were tested for gas throughput.
[0148] The hollow fiber membranes prepared in the examples or comparative examples were used as raw materials and assembled into a membrane with an area of 0.1 mm 2 The component is used as a sample to detect the gas flux.
[0149] Gas with a pressure of 0.1 MPa was introduced into the inlet of the component. The gases were oxygen and carbon dioxide respectively. The outlet of the component was connected to a flow meter to record the gas flux of the component per unit time.
[0150] Generally speaking, the larger the gas flux, the higher the degassing efficiency of the component, and correspondingly, the higher the degassing efficiency of the hollow fiber membrane.
[0151] The hollow fiber membranes prepared in the examples or comparative examples were used as raw materials to assemble the membranes with an area of 0.65 mm 2The components are connected with the dissolved oxygen meter, water circuit and components for testing. The water circuit is used to transport the degassed liquid, the components are used to degas the degassed liquid, and the dissolved oxygen meter is used to detect the oxygen content of the degassed liquid after degassing.
[0152] The degassing liquid is deionized water and its temperature is 25° C. The inside of the membrane is vacuum purged.
[0153] Step 1: Detect the initial oxygen content of the degassed liquid. Pump the degassed liquid into the water circuit. At this time, turn off the vacuum equipment to make the inner side of the membrane at normal pressure. The degassed liquid passes through the assembly (without degassing) and then passes through the dissolved oxygen meter. Keep the flow rate of the degassed liquid into the dissolved oxygen meter at about 1.8 GLH. Observe the changes in the dissolved oxygen reading on the dissolved oxygen meter in real time. After the reading of the dissolved oxygen meter stabilizes (the reading of the dissolved oxygen meter changes by less than 1% within 5 minutes), read the dissolved oxygen reading on the dissolved oxygen meter.
[0154] Step 2, detect the final oxygen content of the degassed liquid after degassing. On the basis of step 1, turn on the vacuum equipment to vacuum purge the inner layer of the membrane to degas the degassed liquid. Keep the vacuum reading at -0.094MPa (50torr) during vacuum purge. Observe the changes in the dissolved oxygen reading on the dissolved oxygen meter in real time. When the reading of the dissolved oxygen meter stabilizes (the reading of the dissolved oxygen meter changes by less than 1% within 5 minutes), it is considered that degassing has begun and reached equilibrium. Read the dissolved oxygen reading on the dissolved oxygen meter. Calculate the deoxygenation efficiency according to the following formula:
[0155]
[0156] Table 3 Gas flow rate of each example
[0157]
[0158]
[0159] The above is only an embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application should be included in the scope of the claims of the present application.
Claims
1. A method for preparing a hollow fiber membrane for degassing, characterized in that: The following steps are involved: S1, spinning, extruding the polyolefin melt to form a semi-molded product with a hollow inner cavity under the action of a cavity-forming fluid; The polyolefin is a homopolymer, has a crystallinity greater than 40%, a melt index of 1-7 g / min@(Tm+20°C, 5kg), a die extrusion temperature of (Tm+10)-(Tm+70)°C, and a die aspect ratio of 2-5; The melting point of the polyolefin is Tm, The polyolefin is at least one of PP, PE and PMP; S2, pre-crystallization, cooling the semi-formed product obtained in step S1 by air cooling to obtain a pre-crystallized semi-finished product; S3, air-cooling crystallization, performing secondary cooling crystallization on the pre-crystallized semi-finished product obtained in step S2 by means of air cooling, and winding to obtain a cooled semi-finished product; S4, annealing and shaping, subjecting the cooled semi-finished product obtained in step S3 to heat shaping treatment, and obtaining a heat-set semi-finished product after cooling; S5, cold drawing to form holes, cold drawing the heat-set semi-finished product obtained in step S4 to obtain a cold-drawn semi-finished product; S6, hot-drawing and hole-expanding, hot-drawing and hole-expanding the cold-drawn semi-finished product obtained in step S5 to obtain a hot-drawn semi-finished product; S7, heat setting, subjecting the hot-drawn semi-finished product obtained in step S6 to secondary heat setting treatment, and obtaining a hollow fiber membrane after cooling.
2. The method for preparing a hollow fiber membrane for degassing according to claim 1, characterized in that: In the step S1, the molecular weight of the polyolefin is 60,000-100,000, and the molecular weight distribution index of the polyolefin is 1-5; the melting process includes: melting, mixing and metering, the melting temperature is (Tm-10)-(Tm+80)°C, the mixing temperature is (Tm+10)-(Tm+100)°C, the metering temperature is (Tm+15)-(Tm+90)°C, and the metering temperature is 5-30°C higher than the die extrusion temperature.
3. The method for preparing a hollow fiber membrane for degassing according to claim 1, characterized in that: In the step S1, when the polyolefin is PP, the isotacticity of the PP is greater than 99%, the crystallinity is 45%-75%, and the melt index is 2-5g / min@(190°C, 5kg); or, when the polyolefin is PE, the PE is mLLDPE, and the density of the mLLDPE is 0.91-0.93g / cm 3 , the molecular weight distribution index is 2-2.5, and the degree of branching is 0.1-0.4; or, when the polyolefin is PMP, the Vicat softening point of the PMP is 160-170°C.
4. The method for preparing a hollow fiber membrane for degassing according to claim 2, characterized in that: In the step S1, when the polyolefin is PP, the melting temperature in the melting process is 160-180°C, the mixing temperature is 180-230°C, and the metering temperature is 190-210°C.
5. The method for preparing a hollow fiber membrane for degassing according to claim 1, characterized in that: In the step S2, the air cooling temperature is 110-220°C lower than the die head temperature, and the air cooling distance of the semi-finished product is 30-1000mm.
6. The method for preparing a hollow fiber membrane for degassing according to claim 1, characterized in that: In the step S3, the cooling length of the pre-crystallization semi-finished product during air cooling is 4-8 m; the air cooling temperature is 40-70° C.; and the air flow velocity during the air cooling crystallization process is 30-60 m / min.
7. The method for preparing a hollow fiber membrane for degassing according to claim 1, characterized in that: The hot drawing temperature in step S6 is at least 60-95° C. higher than the cold drawing temperature in step S5; the hot drawing speed is 5%-15%, preferably 10% of the cold drawing speed; and the hot drawing has a stretching multiple of 2-6 times that of the cold drawing.
8. The method for preparing a hollow fiber membrane for degassing according to claim 1, characterized in that: In the step S5, the cold drawing temperature is 25-80° C. higher than the glass transition temperature of the polyolefin; the cold drawing speed is 10-30% / min; and the cold drawing stretching ratio is 20%-40%.
9. The method for preparing a hollow fiber membrane for degassing according to claim 1, characterized in that: In the step S6, the heat-drawing temperature is 80-160° C.; the stretching ratio of the heat-drawing is 80%-120%; and the heat-drawing speed is 0.3-1.3% / min.
10. The method for preparing a hollow fiber membrane for degassing according to claim 1, characterized in that: In step S4, the annealing process is performed to reduce the temperature to 75-150° C., the annealing time is 20-50 min, and the draft ratio is 0.5%-2%; In the step S7, the heat setting temperature is 5-30° C. higher than the annealing temperature; and the heat setting time is 0.5-3 min.
Citation Information
Patent Citations
Polypropylene hollow fiber micro-pore membrane preparation method
CN107998903A
Cited By
Solvent-free small-aperture polyethylene hollow fiber membrane and preparation method thereof
CN121513658A